APPLICATION PROCESS MODIFICATION OF IMAGE (PICTURE) BY USING THE SOFTWARE ADOBE PHOTOSHOP 7.0 - Denny Chermawan; Elly Agustina J.,S.Kom.,MMSI (Jurnal Sistem Informasi, 2005)
In a modification of an image using Adobe Photoshop 7.0 software we can use the special effects available in the software. Where we can use it easily and creatively with less time and cost is cheap enough to modify an image. To obtain results with good color quality depends on the printer used, the better the quality of the printer the better the results.